Pengabdian Terhadap Masyarakat: Optimalisasi Penulisan Karya Ilmiah Mahasiswa melalui Pemanfaatan Aplikasi Mendeley: Pengabdian - Janwar Tambunan; Lois Oinike Tambunan; Ria Retno Dewi Sartika Manik (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Scientific writing is one of the essential competencies that students must possess, yet it is often hindered by difficulties in managing references and proper citations. This community service aims to enhance students’ ability to write scientific papers systematically and efficiently through the utilization of Mendeley as a reference management tool. The activities were conducted in the form of workshops and hands-on practice using Mendeley, covering installation, literature management, and the creation of citations and bibliographies according to academic standards. The methods employed included a combination of demonstration, discussion, and direct practice with student participants at HKBP Nommensen University Pematangsiantar. The results of the community service indicated a significant improvement in students’ skills in managing references, facilitating citation writing, and accelerating the process of preparing scientific papers. Thus, the use of Mendeley can serve as an effective strategy to support students’ academic productivity and enhance the quality of scientific writing